2022
DOI: 10.3390/jpm12040532
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Combined Intrarenal Surgery Versus Percutaneous Nephrolithotomy for Complex Renal Stones: A Systematic Review and Meta-Analysis

Abstract: Background: Endoscopic combined intrarenal surgery (ECIRS) adds ureteroscopic vision to percutaneous nephrolithotomy (PCNL), which can be helpful when dealing with complex renal stones. Yet, there is still no consensus on the superiority of ECIRS. We aimed to critically analyze the available evidence of studies comparing efficacy, safety, bleeding risk, and efficiency of ECIRS and PCNL. Methods: We searched for studies comparing efficacy (initial and final stone-free rate), safety (postoperative fever, overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…According to the obtained data, in the ECIRS groups compared to PNL in mono-mode, there was a better result of primary and final SFR, fewer complications and the need for blood transfusion. In the analysis of these methods in the «mini-version», there was an additional reduction in the length of hospital stay in the group of mini-ECIRS in comparison with the mini-PNL in mono-mode [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the obtained data, in the ECIRS groups compared to PNL in mono-mode, there was a better result of primary and final SFR, fewer complications and the need for blood transfusion. In the analysis of these methods in the «mini-version», there was an additional reduction in the length of hospital stay in the group of mini-ECIRS in comparison with the mini-PNL in mono-mode [42].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the problem of high cost of ECIRS, mentioned in the study of H. D. Jung et al, where the authors pointed out the difficulties in calculating the cost of these procedures, which can be problematic for the hospital [17]. Thirdly, when combining the two procedures, the surgery duration of ECIRS is sometimes considered longer, but a number of studies have not found a significant difference in the surgery duration between ECIRS and PNL [35,42].…”
Section: Resultsmentioning
confidence: 99%
“…The authors conclude that this novel technique brings better stone free rates and fewer complications and requires less blood transfusions compared to PCNL alone. The devices used for lithotripsy are not compared and no comment is made in this direction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk is always the most important consideration for surgeons. Therefore, many review articles and meta-analyses have been published comparing PCNL with other endoscopic methods of surgery such as ECIRS, which has a better stone clearance rate, fewer complications, and less blood transfusion compared with PCNL [ 10 ]. However, due to its cost, operation position and need for two groups of urologists, not many patients are ultimately suitable for ECIRS.…”
Section: Discussionmentioning
confidence: 99%